21st CENTURY CORPORATE GOVERNANCE: BALANCING SHAREHOLDERS’ AND STAKEHOLDERS’ INTERESTS - Nangoy, Stanley (JBE (Journal of Business and Economics); Volume 13 No.2, 2014 JBE UNKLAB, 2014)
Corporate governance is about the way in which boards oversee the running of a company by its managers, and how board members are in turn accountable to shareholders and the company. This has implications for company behavior towards employees, shareholders, customers and creditors. Good corporate governance plays a vital role in underpinning the integrity and efficiency of financial markets. Poor corporate governance weakens a company’s potential and at worst can pave the way for financial difficulties and even fraud. Corporate governance is used by many companies to ensure that the relationship between management and their stakeholders is kept at a professional level. Just as the name governance suggests authority, the companies use this method to ensure that the company is not involved in any conflict with its stakeholders and in the case where it happens, there is a mechanism of how to solve them. It helps in ensuring discipline within the organization. Good corporate governance should provide proper incentives for the board and management to pursue objectives that are in the interests of the company and its stakeholders and should facilitate effective monitoring. If companies are well governed, they will usually outperform other companies and will be able to attract investors whose support can help to finance further growth.